Model of inactivation of Campylobacter jejuni in poultry scalding - Osiriphun,S. (Elsevier Limited, 2015)
The purpose of this study was to develop a model of inactivation of Campylobacter jejuni in industrial scalding of chickens. Models can be used as a guide for broiler slaughterhouse operations for reducing levels of C. jejuni contamination on broiler carcasses. Mean concentrations of C. jejuni in terms of colony forming units (CFU) in scald tank water and in carcass rinse solution after scalding were 2.90 ± 0.07 and 3.86 ± 0.11 LogCFU/mL, respectively. Scald tank water temperature, flow rate, pH, and total solids in scalding process water were 54.15 ± 0.2 °C, 172.0 ± 8.4 L/min, 8.0 ± 0.01, and 2565 ± 114.3 mg/L, respectively. Inactivation models were developed by using mass balances and literature data for inactivation kinetics, of Campylobacter and the Arrhenius equation. Results of the inactivation models of scalding process indicate that high temperature and short time (less than 2 min) of scalding process were effective in reducing the number of viable cells. For this experimental data more than 50% of the Campylobacter are inactivated on surfaces of the chickens. The model fits the experimental data well and the values of the estimated parameters provide insight for this process. The model can be used for process design and potential process modifications. © 2011 Elsevier Ltd. All rights reserved.